Let's calculate the derivative
(u/v)'=(u'v-uv')/v^2
Here, u=e^x ; =>u'=e^x
v=x-e^x => ; v'=1-e^x
therefore, f'(x)=(e^x(x-e^x)-e^x(1-e^x))/(x-e^x)^2
=(xe^x-e^(2x)-e^x+e^(2x))/(x-e^x)^2=(xe^x-e^x)/(x-e^x)^2
=(e^x(x-1))/(x-e^x)^2
f'(x)=0 when x=1
Let's do a sign chart
color(white)(aaaa)xcolor(white)(aaaaa)-oocolor(white)(aaaaa)0color(white)(aaaaa)1color(white)(aaaaa)+oo
color(white)(aaaa)f'(x)color(white)(aaaaaaa)-color(white)(aaaaa)-color(white)(aaa)+
color(white)(aaaa)f(x)color(white)(aaaaaaaa)darrcolor(white)(aaaaa)darrcolor(white)(aaa)uarr
As the curve is decreasing from -oo to 1, the curve is convex at x=0
graph{e^x/(x-e^x) [-5.546, 5.55, -2.773, 2.774]}